THE REVELATORY TEXT: interpreting the new testament sacred scripture. - SCHNEIDERS, Sandra, M (A DIVISION COLLINS PUBLISHERS HARPER SAN FRANCISCO, 1991)
In this new edition of her major study of the New Testament, Sandra Schneiders proposes a comprehensive hermeneutical theory for New Testament interpretation, which takes full account of the Bible as both sacred Scripture and as a historical-literary classic